CREATING THE BEST ROUTING BY HEURISTIC ALGORITHM - ŞİRİN, Mehmet and ALTINTAŞ, Tuğba and GÜNEŞ, Ali (International Journal of Engineering Technologies and Management Research, 2017)
In this study, Travelling Salesman Problem (TSP), an NP-hard problem, is addressed. In order to get the best results with a view to directing TSP heuristics, the ant colony algorithm was used for solution purposes. The purpose was to solve the problem of setting a course for the bread distribution trucks of Istanbul Halk Ekmek (Public Bread) Company using the ant colony algorithm on TSP. A liquid called Pheromone, which ants release in order to establish communication among them, is known as the most fundamental matter to provide this communication. In this research, artificial ants, which function with the logic of finding the shortest path in the area where they are located, were utilized. The purpose of our programme is to determine the shortest route for the arrival of the distribution trucks to the kiosks where bread is sold to the public. The route developed by the programme is displayed over Google maps. Motivation/Background: Explain the importance of the problem investigated in the paper. Include here a statement of the main research question. Method: Give a short account of the most important methods used in your investigation. Results: Present the main results reported in the paper. Conclusions: Briefly present the conclusions and importance of the results. Concisely summarize the study’s implications. Please do not include any citations in the abstract.